Phenolic compounds modulation in β-farnesene fed-batch fermentation using sugarcane syrup as feedstock - Carvalho, Luís Carlos (2022)
Sugarcane syrup is the feedstock used in the industrial production of β-farnesene through Saccharomyces cerevisiae fermentation. However, it contains phenolic compounds, which may interfere with yeast performance. The aim of this work was to modulate the transfer of phenolic compounds from sugarcane syrup to the broth, throughout 13 days of β-farnesene fed-batch fermentation in 2-L bioreactors. This was accomplished by applying two mathematical calculations: a mass balance and the Weibull kinetic model. The concentrations of most phenolic compounds increased until day 3 of fermentation and then remained constant until the end of the process. However, quantities of hydroxybenzaldehyde, protocatechuic, caffeic, ferulic and p-coumaric acids, decreased after day 2. The Weibull model exhibited better fit to the data, with an R2 of 0.85 or higher. This work provides for the first time a model describing phenolic accumulation in β-farnesene fermentation, which can be a valuable tool to apply in similar processes.